FEATURES OF UGLINESS IN JEAN-MICHEL BASQUIAT'S DRAWINGS - Assist. Lect. Hawra Ali Abed Muhammad Regan , Prof. Dr. Ali Shanawa Wadi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research investigates (the features of ugliness in the drawings of jean-michel basquiat), as (Basquiat) is one of the most famous and popular artists in the formation of the postmodern phase, which in turn is a reaction to all the modernist data and its opposition, as it was born out of doubt and suspicion in the mind and Facts and the idea of ??existence, which drew its strength from philosophy from the middle of the twentieth century and the decades that followed, and its artists often mix between different artistic and popular styles, and with individual experiences that raise important issues with an artistic shift away from all previous idealistic labels, and graffiti art best embodies the above mentioned in This modest research is one of the most prominent phenomena in the contemporary time, the artist (Jean-Michel Basquiat), who passed away two decades ago and until this moment his works are being auctioned, adding that they are the biggest focus of questions and raise questions. In light of this, the research consists of the methodological framework of the research, starting with the problem, the importance of the research, its goal and its limits. It also includes the theoretical framework of the research and research procedures and ends with the most important results and conclusions.